Do Employees boost opportunities to compete abroad? A longitudinal study of family and non-family firms. Issue 5 (October 2022) - Campos-García, Irene; Muñoz-Bullón, Fernando; Sanchez-Bueno, Maria J.; Zúñiga-Vicente, José Ángel
Abstract: This study sheds light on the contingent effect that employee human capital may have on the relationship between family involvement and internationalisation via exporting —both in terms of entry mode ( how to export) and degree ( how much to export). We formulate several hypotheses by drawing mainly on arguments from the resource-based view and stewardship theory. The empirical setting is a large sample of Spanish manufacturing firms (family and non-family) operating between 1991 and 2016. Our results reveal that the positive (negative) relationship between family involvement and export intensity (direct exporting) is boosted (mitigated) at higher levels of employee human capital. Our findings thus provide statistical support for a positive and significant contingent approach to the effect human capital has on the connection between family involvement and internationalisation.